Do high school STEM courses prepare non-college bound youth for jobs in the STEM economy?. Issue 3 (4th May 2017) - Bozick, Robert; Srinivasan, Sinduja; Gottfried, Michael
ABSTRACT: Our study assesses whether high school science, technology, engineering, and mathematics (STEM) courses provide non-college bound youth with the skills and training necessary to successfully transition from high school into the STEM economy. Specifically, our study estimates the effects that advanced math, advanced science, engineering, and computer science courses in high school have on the probability that non-college bound youth will obtain employment in the STEM economy and on wages within two years of graduating from high school. Our findings indicate that STEM coursework is unrelated with the probability of securing a job in the STEM economy and is unrelated with wages two years post high school graduation.